Az Egis Gyógyszertár Zrt. kontrolling rendszerének bemutatása - Pasics Júlia Petra (2018)
When choosing my thesis topic, it was really important for me to elaborate a topic which I feel the nearest to me. That is why I chose to introduce the controlling system of my workplace, the plant of Egis Gyógyszergyár Zrt. in Körmend. When writing my thesis, it was a key aspect to fully introduce the company’s con-trolling system for the readers. In the first part of my thesis not only the plant in Körmend was examined, but the whole company as well. Egis Gyógyszergyár Zrt. was introduced in the first phase in which I dealt with the company’s history, its organisational structure, and its activities. The way I see, the introduction of a company is closely related to its industry analysis, and therefore I also examined it from the viewpoint of Egis Gyógyszergyár. To do so I used Porter’ Five Forces model which I had got to know during my studies. The second part of my thesis includes the introduction of the company’s controlling group as well as that of the softwares used by them. It contains inter alia the literature re-view, which was examined in case of Egis as well. This examination includes the topic of the role of controlling within the organisation, which was analysed generally and then compared to the practice of the company. I briefly introduced the use of SAP and of IBM Cognos TM1 system applied by the company so that the main part of my thesis could be understood. The main part of my thesis was about the cost controlling of the plant in Körmend, together with its related maintenance cost report. At the end of this part I made some rec-ommendations for the company. Based on the information made available for me, I intro-duced in more details the direct cost controlling, which I made based on the company’s product management and planning function. This module was presented by the model’s main steps (production order, booking, feedback, product calculation, production settle-ment). A larger part in case of both the company and my thesis was about general cost controlling to which is related the more practical part, the elaboration of maintenance re-port. Within general cost controlling I dealt with the followings: the calculation of cost types and cost centres applied by the company, budget management, CO order and the monthly closes done by the group. An integrated part of this latter is to compile the maintenance report which is done monthly for the top and middle managers by the con-trolling. I compared the old and the new reports, and after having presented the steps of compiling the report, I introduced our joint report. Finally, based on the process, I wrote my recommendations for the company.